Biowaiver as a Bioequivalence Study Option - E. A. Volkova; Yu. V. Medvedev; E. N. Fisher; I. E. Shohin (Регуляторные исследования и экспертиза лекарственных средств, 2024)
SCIENTIFIC RELEVANCE. Biowaiver is a procedure for establishing the bioequivalence of generic and reference products without in vivo studies. Regulatory requirements for this procedure, as described in a variety of documents, differ in certain features and aspects. These differences need to be analysed.AIM. The aim was to compare international and Russian regulatory approaches to the Biopharmaceutics Classification System-based biowaivers, provide recommendations on comparative dissolution testing, and outline opportunities for streamlining the regulatory framework of the Eurasian Economic Union (EAEU).DISCUSSION. In this article, the authors analyse biowaiver requirements and describe procedures for assessing the permeability and pH-dependent solubility of medicines, comparing dissolution profiles in various media that simulate the gastrointestinal environment, and interpreting test results. This paper shows the role of excipients in the solubility and permeability of an active substance.CONCLUSIONS. The authors recommend a methodological approach to the biowaiver procedure for replacing in vivo bioequivalence studies with in vitro tests under the current EAEU regulatory framework and list the characteristics of medicines that limit the applicability of the procedure. In conclusion, this article provides a rationale for harmonising the existing guidelines and requirements.